Utility of fibroblasts derived from broncho-alveolar lavage of patients with idiopathic pulmonary fibrosis or related disorders to develop in vitro models - Paolo Giannoni; Emanuela Barisione; Marco Grosso; Daniela de Totero (Open Exploration Publishing Inc., 2023)
Broncho-alveolar lavage (BAL) represents a safe tool for the differential diagnosis of various pulmonary fibrotic diseases. Idiopathic pulmonary fibrosis (IPF) belongs to a heterogeneous group of diseases, interstitial lung disease (ILD), presenting a progressive impairment of pulmonary functions. IPF is characterized by the excessive accumulation of extracellular matrix (ECM) in the alveolar parenchyma that may lead to irreversible pulmonary remodeling. Although the exact pathogenetic mechanisms leading to IPF development are still unclear it has been demonstrated that fibroblasts differentiating toward myofibroblasts are the major actors involved in this process. The possibility of obtaining and expanding fibroblasts from the BAL of ILD patients for research purposes has been recently explored. This approach is discussed here as a reliable chance, helpful to advance the scientific community knowledge and to devise two- and three-dimensional (2D/3D) pre-clinical in vitro models of these diseases, further overcoming technical and ethical concerns related to the use of fibroblasts derived from tissue biopsy.